Global mortality burden of lung cancer and mesothelioma attributable to occupational asbestos exposure and the impact of national asbestos ban policies: a population-based study, 1990–2021 - Wei Wang; Jun Liu; Hengrui Liang; Wenhua Liang; Jianxing He; Xiwen Liu; Shen Lao; Wang-Zhong Li (BMJ Public Health, 2025)
Introduction Asbestos-related thoracic cancers (ARTCs), including asbestos-related lung cancer and mesothelioma, constitute the majority of deaths due to asbestos exposure. This study evaluates the global mortality burden of ARTCs and the influence of national asbestos ban policies.Methods We used data from the Global Burden of Diseases Study 2021 to estimate the mortality burden of ARTCs and analyse trends from 1990 to 2021, stratified by sex, location and sociodemographic index (SDI) quintile. Decomposition analysis identified contributors to changes in the ARTC burden, and future projections were made using the Bayesian age-period-cohort model. The relationship among asbestos ban policies, SDI and ARTC deaths was also examined.Results In 2021, an estimated 216 535 deaths from ARTCs (including 29 619 from mesothelioma and 189 398 from lung cancer) resulted in an age-standardised mortality rate (ASMR) of 4.1 per 100 000 population, accounting for over 95% of deaths from asbestos-related cancers. Notable variation in ARTC deaths was observed across age, sex, location and SDI quintile, with higher ASMR among men, older adults and countries with higher SDI. From 1990 to 2021, there was a global decline in ASMR from ARTCs, particularly among men and in cases of asbestos-related lung cancer, although increases were noted in low to middle SDI quintiles. Despite a consistent reduction in ASMR, the absolute number of ARTC deaths is rising due to population growth and ageing. Countries with implemented asbestos bans have historically and currently faced higher ARTC burdens. A positive impact of asbestos ban policies on reducing ASMR from ARTCs was observed, although the effects take decades to manifest.Conclusions Substantial geographic and sociodemographic disparities exist in the burden and trends of ARTCs. Countries with asbestos bans have historically faced higher ARTC burdens, and while these bans significantly reduce ASMR from ARTCs, the benefits take decades to become evident.